Pengaruh CR Dan DER Terhadap ROA Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia - Saryo Widodo,; Desy Arigawati,; Merintan Berliana Simbolon,; Adelina Suryati, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the effect of Current Ratio (CR) and Debt To Equity Ratio (DER) on Return On Assets (ROA) both partially and simultaneously. This research was conducted at the Indonesian Stock Exchange. The population in this study was the transportation sector companies. The sample used was thirty-six and data analysis for hypothesis testing was carried out using multiple regression. The analysis tool used is the Statistical Package the Social Science (SPSS) 22. The results of the study indicate that the Current Ratio (CR) and Debt To Equity Ratio (DER) simultaneously or together have a significant effect on Return On Asset (ROA). Partially shows that the Current Ratio (CR) has a positive and significant effect on Return On Asset (ROA) with a pair value (t test) of 0.032 <0.05 while the Debt To Equity Ratio (DER) does not have a significant effect on Return On Asset (ROA) with a pair value (t test) of 0.297> 0.05. Furthermore, based on the adjusted r square, it can be seen that the effect of the Current Ratio (CR) and Debt To Equity Ratio (DER) can be explained by 18.7%.